Sociocultural factors associated with the development of postnatal anxiety symptoms. (2nd June 2019) - Mohammad, Khitam; Al-Farajat, Eqbal; Creedy, Debra; Gamble, Jenny
Abstract : Background: Postnatal anxiety is relatively common when transitioning to parenthood; however, there are relatively few studies assessing postnatal anxiety in Middle Eastern women. Aim: To identify the prevalence of postnatal anxiety among Jordanian women and associated sociocultural factors. Method: A descriptive cross-sectional design was used with 324 women. Participants completed the Depression, Anxiety, and Stress Scale (DASS) and Maternity Social Support Scale at 6-8 weeks postpartum in addition to a sociodemographic data form. Findings: Some 45.4% of women scored above 'mild' on the DASS scale. Postnatal anxiety was significantly associated with low levels of support, giving birth to a female baby, financial difficulties, and having four or more children. Findings revealed a high level of postnatal anxiety among Jordanian women. Conclusion: There is a need for routine assessment, ongoing support, counselling and emotional care, which are important to enhance maternal satisfaction and psychological wellbeing.